Effect of soil salinity on survival, growth and chlorophyll contents of 'Kurukkan'mango (Mangifera indica) - SRIVASTAV, MANISH; DUBEY, A K; PANDEY, R N; DESNMUKH, P S (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2003-05 to examine the effect of graded levels of artificially developed soil saIinity dominated by chloride, sulphate and carbonate ions on survival, growth and chlorophyll contents of the 'Kurukkan' seedlings. Graded levels of soil salinity (-1.0, 2.0,4.0 and 6.0 dS/m) were maintained separately by different salt combinations. The survival of seedlings declined significantly with the increasing levels of salinity in all salt combinations.